Penerapan Standart Keselamatan Dan Kesehatan Kerja (K3) Proyek Jasa Konstruksi (Studi Kasus: Pembangunan Gedung Kantor Pemkab Lamongan) - Nurainiyah Nurainiyah; Hammam Rofiqi Agustapraja (Civilla : Jurnal Teknik Sipil Universitas Islam Lamongan, 2019)
Lamongan is a developing city, as well as its development sector. Either simple or high technology development cannot avoid the workplace accidents risk. Therefor, implementing safety and health management is very important because it can create a good and safe working environment. However,it will not work if there is no commitment from all parties involved in the project. The purpose of this study is to assess the application of Occupational Health and Safety (K3) management system.This study uses questionnaire data. The respondents are from the employers of Lamongan District Office building project. This study uses SPSS program and uses validity and reliability test.The result of this research is that the project has implemented K3 well, although there are still some obstacles to its implementation. From the questionnaire result, it proves that more than 50% of the respondents choose to agree with the statement in the questionnaire submitted by the researcher. The test questionnaire is valid and reliable with Cronbach Alpha ranging from 0.617-0.867 which means greater than 0.60.